2015
DOI: 10.3109/08037051.2015.1030902
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prophylactic migraine treatment on arterial stiffness

Abstract: The increased PWV demonstrated in migraine patients in this study stands out as an additional parameter elucidating endothelial dysfunction in these patients. Decreasing the number of migraine attacks with prophylactic treatment may reduce PWV and decrease cardiovascular risk in long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…24 Hence, we cannot rule out the interference of specified treatments in PWV measurements or other parameters, as we did not include these data in the analysis. One study showed that prophylactic migraine drugs improve PWV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…24 Hence, we cannot rule out the interference of specified treatments in PWV measurements or other parameters, as we did not include these data in the analysis. One study showed that prophylactic migraine drugs improve PWV.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that prophylactic migraine drugs improve PWV. 24 Hence, we cannot rule out the interference of specified treatments in PWV measurements or other parameters, as we did not include these data in the analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to that study it can be said that migraine patients with aura have a higher cardiovascular risk. Dogan et al compared migraine patients without cardiovascular risk factors with a control group and found higher CFPWV in the migraine patients 30 . In the current study, no difference was determined between patients with and without aura.…”
Section: Discussionmentioning
confidence: 99%